Pursuing Lifelong Dreams: Published Novelists Who First Succeed After 40 - Jennifer Murray (Adult Education Research Conference, 2014)
Pithy but dire quotes on the perils of writing like this one abound by published writers. Then there is waiting for publication. What quality of motivation did Dick Wimmer possess to endure 162 rejections over the course of 25 years until his novel, Irish Wine, was finally published in 1989 (Hievsi, 2001)? What meaning did Irish Wine hold for him that he was determined not only to write it, but that the world should read it? Many people think they want to be a writer, someday. Only a small number ever decide that someday starts now. Fewer people finish writing their novel manuscripts; fewer still publish them.